Pengaruh Kombinasi Spiritual Emotional Freedom Tehnique Dan Terapi Murottal Al-Quran Terhadap Penurunan Kadar Gula Darah Pada Penderita DM Tipe II: Keperawatan - Tri Wanda Agustina; Tri Nataliswati; Marsaid; Maria Diah Ciptaningtyas (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MOJOKERTO), 2025)
Diabetes mellitus is a metabolic disorder characterized by high blood sugar levels. If left untreated, it can cause damage to organs such as the heart, brain, kidneys, eyes, nerves, and even gangrene, which carries a risk of amputation. SEFT therapy and Quranic recitation therapy can be used by people with Type II diabetes to promote relaxation, which can help reduce emotional tension and stress. The production of these endorphins hormone promotes feelings of peace and relaxation, thereby reducing the amount of cortisol produced by the adrenal glands, all of which play a role in lowering blood glucose levels. This study aims to determine the effect of this therapy on patients with type II diabetes mellitus, used a time series design with a one-group pretest-posttest approach. 54 respondents were purposively selected. The combination of SEFT and Murottal Al-Qur'an therapy was administered for 15 minutes, three times over three days. Data collection was conducted using questionnaires and blood sugar level measurements. On day 1 pretest, the mean had blood sugar levels of 286.41 mg/dL, indicating hyperglycemia. Before therapy on day 2, blood sugar levels decreased to 208.52 mg/dL. After therapy, blood sugar levels dropped to 252.78 mg/dL on posttest day 1 and 173.00 mg/dL on posttest day 2. The Wilcoxon test results significant decrease in blood sugar levels, with a p-value of 0.000 (<0.05). Nurses working in the Inpatient Ward should increase their knowledge by attending training SEFT and Al-Qur'an Murottal Therapy which can be used as alternative supporting interventions for type II diabetes mellitus sufferers